It takes all of us working towards Academic Integrity - Kruithof, Koos (Septentrio Conference Series, 2017)
The rise of plagiarism is often related to the shift from an analogue to a digital society. Due to the availability of information which makes it possible to discover quickly lots of information on specific subjects it is easy for learners to take information from another source. This fact shows that Academic Integrity is a challenge for those who are concerned with quality of education and research. Academic Integrity can be difficult to measure. There is also a risk that Academic Integrity is being taken for granted. The process of defining what Academic Integrity is and being both visible and practical in demonstrating its impact can do much to reconfirm its importance. There is work to be done and guidance needed. Examples and clear definitions with plans for execution are needed now. These examples and definitions are already present in the academic community. The challenge is to give this community the confidence to share their best practices with their peer institutions. For learners, the importance of Academic Integrity goes beyond a set of rules with which to understand black and white behaviour; Academic Integrity Policy is the rock which helps to understand what to do in grey situations. The temptation and ease with which learners can take short sighted decisions can be better combatted with a more thorough understanding of the long term impact for themselves, their academic work, career and society more widely. But how to start the conversation with learners about integrity and what do we say? How can we prepare learners for an academic life?